REBRANDING SEBAGAI PROSES PERUBAHAN ORGANISASI - Nadila Aprilyani; Andi Azhar (UM. Bengkulu, 2026)
This study aims to analyze rebranding as a process of organizational change using a narrative inquiry approach in the food and beverage industry, specifically at Trilogi Coffee and Eatery in Bengkulu City, which experienced a brand identity crisis. This study employed a qualitative approach with a narrative inquiry strategy. The research subjects consisted of 6–8 internal organizational actors, including owners and frontline employees, and approximately 20 consumers as supporting informants for data triangulation. Data collection techniques included in-depth interviews, participant observation, and organizational document analysis. Data analysis used thematic narrative analysis through transcription, narrative coding, plot construction, theme identification, and interpretation of organizational change meanings. The results indicate that rebranding is not merely a change in visual identity but a holistic organizational change process. The rebranding process began with the unfreezing stage marked by awareness of brand identity crisis, followed by the changing stage involving implementation of a new identity, operational restructuring, and organizational culture transformation, and the refreezing stage through internalization of new values and identity by internal actors. Rebranding was interpreted as a strategic effort to rebuild organizational legitimacy, strengthen brand identity, and ensure business sustainability. Internal actors’ narratives revealed that rebranding success was strongly influenced by internal communication, employee involvement, and alignment between organizational identity and the new brand identity. Keywords: Rebranding, organizational change, brand identity, narrative inquiry, food and beverage industry.